Sustainability in Malaysian palm oil: a review on manufacturing perspective - Ilyana, Abdullah; Wan Hasrulnizzam, Wan Mahmood; Muhammad Hafidz Fazli , Md Fauadi; Mohd Nizam , Ab Rahman; Fathiyah, Ahmad Jali (2015)
The increasing demand of palm oil product has emerged the industry to develop a sustainability strategy on the unintended social, environmental, and economic consequences of rapid population growth, economic growth and consumption of the natural resources. This paper reviews the manufacturing perspective on the current sustainability effort and identifies the key drivers for sustainability, particularly in Malaysia who has controlled almost 50 percent of the global export market shares. It revealed to date research on sustainability in general palm oil manufacturing (or palm oil mill) which involved empty fruit bunch, crude palm oil, crude palm kernel oil, fibre, shells, refinery process and palm oil waste management. The findings of the study suggest that manufacturing sustainability in Malaysian palm oil manufacturing is driven by three main elements; environmental consciousness, economic escalation, and social commitment. Among these three elements, research on environmental consciousness and economic escalation are the most explored. Meanwhile, social commitment shows a lesser amount of publications. This study can be helpful for palm oil manufacturer particularly in Malaysia to recognize their opportunities and threats in efforts to enhance business profile and corporate reputation, and market growth without disregard the environmental and social impacts.